Message in a bottle - Zenatti, Valerie; Hunter, Adriana (London: Bloomsbury, 2008)
An eye-opening novel from award-winning author Valerie Zenatti about two young people whose defiant relationship crosses dangerous boundaries.
Keywords: Arab-Israeli conflict -- Social aspects -- Fiction; Teenage girls -- Israel -- Fiction; Young adult fiction